The Glucosamine‐derivative NAPA Suppresses MAPK Activation and Restores Collagen Deposition in Human Diploid Fibroblasts Challenged with Environmental Levels of UVB. (17th December 2019) - Lopreiato, Mariangela; Cocchiola, Rossana; Falcucci, Susanna; Leopizzi, Martina; Cardone, Michele; Di Maio, Valeria; Brocco, Umberto; D'Orazi, Valerio; Calvieri, Stefano; Scandurra, Roberto; De Marco, Federico; Scotto d'Abusco, Anna
Abstract: The ultraviolet (UV) component of solar radiation is the driving force of life on earth, but it can cause photoaging and skin cancer. In this study, we investigated the effects of the glucosamine‐derivative 2‐(N‐Acetyl)‐L‐phenylalanylamido‐2‐deoxy‐β‐D‐glucose (NAPA) on human primary fibroblasts (FBs) stimulated in vitro with environmental levels of UVB radiation. FBs were irradiated with 0.04 J cm −2 UVB dose, which resulted a mild dosage as shown by the cell viability and ROS production measurement. This environmental UVB dose induced activation of MAP kinase ERK 1/2, the stimulation of c‐fos and at lower extent of c‐jun, and in turn AP‐1‐dependent up‐regulation of pro‐inflammatory factors IL‐6 and IL‐8 and suppression of collagen type I expression. On the contrary, 0.04 J cm −2 UVB dose was not able to stimulate metalloprotease production. NAPA treatment was able to suppress the up‐regulation of IL‐6 and IL‐8 via the inhibition of MAP kinase ERK phosphorylation and the following AP‐1 activation, and was able to attenuate the collagen type I down‐regulation induced by the UVBs. Taken together, our results show that NAPA, considering its dual action on suppression of inflammation and stimulation of collagen type I production, represents an interesting candidate as a new photoprotective and photorepairing agents. Abstract : Human primary fibroblast were irradiated with 0.04 J cm −2 UVB dose, which resulted a mild dosage as shown by ROS production measurement. This environmental UVB dose induced activation of MAP kinase ERK 1/2, the stimulation of c‐fos and at lower extent of c‐jun, and in turn AP‐1‐dependent up‐regulation of IL‐6, IL‐8, Cox‐2 and suppression of collagen type I expression. Pretreatment of fibroblasto with glucosamine‐derivative NAPA was able to suppress the increase of IL‐6 and IL‐8 via the inhibition of MAP kinase ERK phosphorylation and to attenuates the collagen type I decrease induced by the UVBs.